Assessment Adaptive Capacity Perubahan Iklim Di Indonesia Guna Mempertahankan Ketahanan Pangan - Rafael Rajagukguk, Matthew; Arrafi Juliannisa, Indri (Ekonomi dan Bisnis, 2025)
Purpose: This study aims to analyze and rank the factors influencing food security in Indonesia under climate change, focusing on the role of variables such as temperature change, drought and land fires, pollution, floods, irrigated rice fields, number of farmers, agricultural GRDP, and number of markets. Design/methodology/approach: The research employs the Multi Criteria Decision Making (MCDM) method using the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), applied to data from 34 provinces in Indonesia. Findings: The results indicate that 17 provinces have positive Phi values, reflecting relatively higher food security, while the other 17 provinces with negative Phi values show greater vulnerability to climate change. Research limitations/implications: The study is limited by the selected variables and secondary data availability, excluding external factors such as government policies, geopolitical conditions, and global market dynamics. This opens opportunities for future research to add new variables or apply the model at the district or city level. Practical implications: The provincial rankings provide a basis for policymakers, practitioners, and stakeholders in designing adaptive strategies to strengthen food security and prioritize interventions and resource allocation. Originality/value: The originality of this study lies in the application of the PROMETHEE method in analyzing food security in Indonesia, highlighting its novelty and importance in supporting sustainable national food security. Paper type: Research paper.   Keywords: Food Security, Adaptive Capacity, Climate Change, PROMETHEE.